ENGLISH TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION AT SMA SWASTA AL MAKSUM - Neni Afrida Sari Harahap; Dinda Nurul Fadillah; Halimahtu Saddiah; Yoga Marcell Karosekali (Indonesian Journal of Education (INJOE), 2025)
This study aimed at investigating the teacher strategies and the implementation of those strategies in teaching reading comprehension at SMA Swasta Al-Maksum Deli Serdang Sumatera Utara. The research conducted uses descriptive qualitative research to collect data from semi-structured interviews and classroom observation techniques involving one English teacher teaching eleventh-grade students. The result of this study shows that several strategies such as Note-taking (highlighting critical vocabulary, guiding students to write difficult words with meanings and examples), Peer tutoring (helping less able readers, pairing stronger and weaker students, small-group discussion to interpret texts collaboratively), Game learning (motivating reading activities, vocabulary and comprehension games, point and reward system to promote active participation), YouTube video materials (providing visual reinforcement, selecting topic-related videos, pre-teaching vocabulary, post-video tasks linking visual content to reading texts). These strategies contribute to addressing problems such as limited literacy skills, low student motivation, and varied levels of comprehension. Consequently, this study provides insight into learning strategies to be adopted to improve learning processes in EFL language learning despite adverse learning conditions such as minimal language literacy skills in learning institutions.